Factors related to spiritual well-being in the last days of life in three East Asian countries: An international multicenter prospective cohort study. (September 2021) - Hiratsuka, Yusuke; Suh, Sang-Yeon; Kim, Sun-Hyun; Cheng, Shao-Yi; Yoon, Seok-Joon; Koh, Su-Jin; Park, Shin Ae; Seo, Ji-Yeon; Kwon, Jung Hye; Park, Jeanno; Park, Youngmin; Hwang, Sun Wook; et al.
Background: Some factors associated with spiritual well-being in dying patients have previously been reported. However, there has been no cross-cultural study comparing factors related to spiritual well-being. The current investigation may shed light on this under-investigated area through a comparison of diverse factors. Aim: We aimed to (1) examine factors associated with spiritual well-being in the last days and (2) compare those factors across three East Asian countries. Design: This is an international multicenter prospective cohort study. Setting/participants: Newly admitted inpatients with far advanced cancer in palliative care units in Japan, Korea and Taiwan were enrolled. Each patient was classified into one of two groups based on spiritual well-being score in the last days of life. Univariate and multivariate analyses were performed to identify the factors related to better spiritual well-being score in each country. Results: A total of 1761 patients treated at 37 palliative care units from January 2017 to September 2018 were analyzed. Seven variables were significant in Japan, three in Korea, and five in Taiwan. "Good death scale [acceptance], " "fatigue" and "expressed wish for hastened death" were unique in Japan. "Visit from a pastoral care worker within 48 h of death" was unique in Korea. "Patient's preferences for place of death, " "dyspnea" and "continuous deep sedation" were unique in Taiwan. Conclusions: This study found novel factors related to spiritual well-being in the last days of life, several of which differed according to country. Recognition of factors associated with spiritual well-being can improve the quality of palliative care.